Development of Improved Vaccine Adjuvants Based on the Saponin Natural Product QS-21 through Chemical Synthesis - Fernández-Tejada, Alberto (Acc Chem Res, 2016)
[Image: see text] Vaccines based on molecular subunit antigens are increasingly being investigated due to their improved safety and more precise targeting compared to classical whole-pathogen vaccines. However, subunit vaccines are inherently less immunogenic; thus, coadministration of an adjuvant to increase the immunogenicity of the antigen is often necessary to elicit a potent immune response. QS-21, an immunostimulatory saponin natural product, has been used as an adjuvant in conjunction with various vaccines in numerous clinical trials, but suffers from several inherent liabilities, including scarcity, chemical instability, and dose-limiting toxicity. Moreover, little is known about its mechanism of action. Over a decade-long effort, beginning at the University of Illinois at Urbana-Champaign and continuing at the Memorial Sloan Kettering Cancer Center (MSKCC), the group of Prof. David Y. Gin accomplished the total synthesis of QS-21 and developed a practical semisynthetic approach to novel variants that overcome the liabilities of the natural product. First, semisynthetic QS-21 variants were designed with stable amide linkages in the acyl chain domain that exhibited comparable in vivo adjuvant activity and lower toxicity than the natural product. Further modifications in the acyl chain domain and truncation of the linear tetrasaccharide domain led to identification of a trisaccharide variant with a simple carboxylic acid side chain that retained potent adjuvant activity, albeit with reemergence of toxicity. Conversely, an acyl chain analogue terminating in a free amine was inactive but enabled chemoselective functionalization with radiolabeled and fluorescent tags, yielding adjuvant-active saponin probes that, unlike inactive congeners, accumulated in the lymph nodes in vaccinated mice and internalized into dendritic cells. Subtle variations in length, stereochemistry, and conformational flexibility around the central glycosidic linkage provided QS-21 variants with adjuvant activities that correlated with specific conformations found in molecular dynamics simulations. Notably, deletion of the entire branched trisaccharide domain afforded potent, truncated saponin variants with negligible toxicity and improved synthetic access, facilitating subsequent investigation of the triterpene core. The triterpene C4-aldehyde substituent, previously proposed to be important for QS-21 adjuvant activity, proved to be dispensable in these truncated saponin variants, while the presence of the C16 hydroxyl group enhanced activity. Novel adjuvant conjugates incorporating the small-molecule immunopotentiator tucaresol at the acyl chain terminus afforded adjuvant-active variants but without significant synergistic enhancement of activity. Finally, a new divergent synthetic approach was developed to provide versatile and streamlined access to additional linear oligosaccharide domain variants with modified sugars and regiochemistries, opening the door to the rapid generation of diverse, synthetically accessible analogues. In this Account, we summarize these multidisciplinary studies at the interface of chemistry, immunology, and medicine, which have provided critical information on the structure–activity relationships (SAR) of this Quillaja saponin class; access to novel, potent, nontoxic adjuvants for use in subunit vaccines; and a powerful platform for investigations into the mechanisms of saponin immunopotentiation.